A novel multiplex PCR assay for simultaneous detection of nine clinically significant bacterial pathogens associated with bovine mastitis. (June 2017) - Ashraf, Aqeela; Imran, Muhammad; Yaqub, Tahir; Tayyab, Muhammad; Shehzad, Wasim; Thomson, Peter C.
Abstract: For rapid and simultaneous detection of nine bovine mastitic pathogens, a sensitive and specific multiplex PCR assay was developed. The assay was standardized using reference strains and validated on mastitic milk cultures which were identified to species level based on 16S rRNA sequencing. Multiplex PCR assay also efficiently detected the target bacterial strains directly from milk. The detection limit of the assay was up to 50 pg for DNA isolated from pure cultures and 10 4 CFU/ml for spiked milk samples. As estimated by latent class analysis, the assay was sensitive up to 88% and specific up to 98% for targeted mastitic pathogens, compared with the bacterial culture method and the 16S rRNA sequence analysis. This novel molecular assay could be useful for monitoring and maintaining the bovine udder health, ensuring the bacteriological safety of milk, and conducting epidemiological studies. Highlights: A single reaction-based multiplex PCR assay was developed for rapid detection of nine mastitis causing bacterial pathogens. The detection limit of the assay was up to 50 pg for DNA isolated from pure cultures and 10 4 CFU/ml for spiked milk samples. The LCA specificity and sensitivity estimates were comparable between our assay and the standard 16S rRNA sequence analysis.